Forestilling og handling - Pyysiäinen, Ilkka (Religionsvidenskabeligt Tidsskrift, 2005)
In this paper I outline the hypothesis that counterintuitive religious beliefs partly acquire their plausibility for the believer from the fact that they guide motor action in rituals. The hypothesis is based on connecting theories of a ‘theory of mind’ with findings about the so-called ‘mirror neurons’ that are activated in certain kinds of motor actions as well as in watching and imitating other people’s similar action.